Sherlock Holmes and Newt Scamander: Incorporating Protected Nonlinear Character Delineation Into Derivative Works - Skoller, Jenna (The Columbia Journal of Law & the Arts, 2015)
Author J.K. Rowling published a book in 2001 under the pseudonym Newt Scamander with an “About the Author” section that provided a brief outline of the fictional author. Prior to this brief biographical section, fans of the Harry Potter universe had only been introduced to the character of Scamander in passing as the author of a required textbook that the main characters purchased. Rowling subsequently announced that she would pen the screenplays for a trilogy of films featuring this very minor character as the lead. Although Rowling is (ostensibly) the sole author of the Harry Potter books and the companion book, Fantastic Beasts and Where to Find Them, she will likely be considered a joint owner of the copyright in the film she is writing. It is foreseeable, therefore, that the copyright in the books and the films might expire at different times, if one of the joint creators of the film dies after Rowling. This, then, would result in the question of when the character of Newt Scamander enters the public domain. If Scamander was a copyrightable character when introduced in the Harry Potter series and companion book, can a portion of his character enter the public domain when those books expire, while the rest of his character remains protected until the expiration of the film’s copyright? This is further complicated by the fact that this development is nonlinear, meaning that the films will focus on Scamander’s youth and young adulthood, while the books only refer to the character after he has already died. This Note focuses on copyright protection of literary characters featured in multiple works, some of which are in the public domain but others of which remain protected. In multiple work circumstances, new character elements are often revealed in these still-copyrighted later works that fundamentally change the way we think of and write about the earlier version of the character. This Note proposes a test for how derivative works featuring such characters should be analyzed for infringement. There are two instances this Note will focus on: first, where the character is not copyrightable in the initial instance in which the character appears in a work, and second, where the character develops over time in a way that changes the reader’s perception of the character in a fundamental way.